Radium isotope assessment of submarine groundwater discharge and associated nutrient inputs in Eastern Liaodong Bay, China - Guo, Qiaona; Zhao, Yue; Li, Mengjun; Liu, Jinhui (Frontiers in Marine Science, 2022)
The accurate assessment of submarine groundwater discharge (SGD) and associated nutrient fluxes plays a significant role in water resources management and ecological environment protection in the coastal area. Currently, Liaodong Bay has become one of the most polluted marine areas in China. However, the nutrient fluxes carried by the SGD and its environmental effects have not yet been thoroughly reported in eastern Liaodong Bay, China. In this study, the distribution of 224Ra/223Ra activity ratio and its influencing factors under the geochemical conditions were explored. The activity of radium was affected by the water type and the geochemical factors. The radium isotopes in seawater were positively correlated with the ratios of Mg2+/Na+ and Ca2+/Na+ but negatively correlated with salinity and SO42−. The average apparent water age was evaluated to be 13.0 days. Furthermore, based on the radium mass balance model, the total average SGD flux was calculated to be 1.31 × 108 m3 day–1. The nutrient fluxes carried by the SGD were 7.16 × 107, 1.01 × 106, 1.61 × 107, 0.92 × 106, and 5.41 × 107 mol day−1 for DIN, DIP, NH4+, NO2−, and NO3−, respectively. The nutrient inputs through the SGD have an average DIN : DIP ratio of 70, which was able to seriously affect the ecological environment. The SGD-derived nutrient fluxes were higher than the local river input, which demonstrated that the SGD was a major source of nutrients affecting regional marine ecosystems.